Negotiating identities: the intersectional identity work of refugee women entrepreneurs - Adeeko, Nkechi Joanne (2021)
This study explores the complex identity work undertaken by women refugee entrepreneurs in the UK. Whilst popular discourse proposes self-employment as an accessible means to integration and autonomy for marginalised people, many refugees engage in entrepreneurial activities to avoid discrimination and disadvantage in the labour market. Drawing on translocational intersectionality to examine the experiences of this under-researched group of women, this thesis examines how the intersection of gender, ethnicity/race, class and other identity markers influence efforts to move from a stigmatised refugee identity to an entrepreneurial identity. In considering the multi-dimensional and dynamic agentic dialogue negotiated with institutional and socio-cultural structures, this study contributes to contextualised scholarship on identity and entrepreneurship. The thesis proposes the following research question: How does engagement in entrepreneurial activities influence the identity construction of refugee women? Underpinned by a critical realist ontology and a social constructionist epistemology, the study is based on five in-depth case studies. It focuses on a UK context as a recipient nation of refugees fleeing persecution in their country of origin. Three important theoretical contributions are made in this thesis. First, the thesis addresses the gap in entrepreneurship scholarship that overlooks the heterogeneity of women entrepreneurs. Thus, it presents as a legitimate subject women refugees from the Global South as they develop and perform their entrepreneurial identities in a Global North setting. Second, it proposes a process of identity construction in the context of refugee women entrepreneurs. Third, in its use of a translocational intersectionality framework, it contributes to greater contextualisation within entrepreneurship literature. In acknowledging institutional, temporal, social, cultural and gendered influences that enable and constrain the entrepreneurial identity process, it exposes notions of stigmatisation and liminality which affect this group of entrepreneurs. Beyond the theoretical contributions, there are practical implications for policy makers and other stakeholder networks. In understanding the experiences of women refugee entrepreneurs, prevalent assumptions can be challenged. This has the potential to lead to a review of services, training programmes and engagement strategies offered to refugee women entrepreneurs.